2021
DOI: 10.1002/zoo.21594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on sperm quality metrics in endangered Mississippi gopher frogs (Lithobates sevosus) from captive populations used for controlled propagation and reintroduction efforts

Abstract: A decline in sperm quality with age is a common prediction of senescence‐based hypotheses and empirical studies. While widely studied across taxa, there is little known on the effect of ageing on sperm quality in amphibians, especially in captive populations used for controlled propagation and reintroduction efforts. Here, we investigated variation in sperm quality metrics (i.e., motility, concentration, and morphology) in the endangered Mississippi gopher frog (Lithobates sevosus) among males of three age cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Furthermore, viable tissue cryobanking should be considered in all future conservation strategies as a source of genetically diverse material that may be required in the future to combat the extinction crisis ( Comizzoli & Holt 2019 ). Great progress is already being made to save endangered species by using ART and aART, as demonstrated by the successful captive propagation and reintroduction using ART of endangered Mississippi gopher frogs in the United States ( Watt et al 2021 ), efforts to breed cheetahs and other endangered felids via ART and aART ( Wildt & Roth 1997 ) and the northern white rhino project to name just a few. However, despite the above example, the current focus is still primarily on mammalian taxa, and there is an urgent need for allowing these technologies to catch up across all others.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, viable tissue cryobanking should be considered in all future conservation strategies as a source of genetically diverse material that may be required in the future to combat the extinction crisis ( Comizzoli & Holt 2019 ). Great progress is already being made to save endangered species by using ART and aART, as demonstrated by the successful captive propagation and reintroduction using ART of endangered Mississippi gopher frogs in the United States ( Watt et al 2021 ), efforts to breed cheetahs and other endangered felids via ART and aART ( Wildt & Roth 1997 ) and the northern white rhino project to name just a few. However, despite the above example, the current focus is still primarily on mammalian taxa, and there is an urgent need for allowing these technologies to catch up across all others.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it is likely that this effect is mediated through the quality of the sperm produced by larger—presumably older—males ( Gasparini et al 2010 ; Roth et al 2010 ). Although age-dependent sperm quality in amphibian species is expected to decrease through senescence ( Hettyey et al 2012 ), a study found that older males displayed the same fertilization capacity (e.g., motility and concentration) as younger males ( Watt et al 2021 ). In addition, it has also been shown that younger males produced more atypical spermatozoa than older males ( Watt et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although age-dependent sperm quality in amphibian species is expected to decrease through senescence ( Hettyey et al 2012 ), a study found that older males displayed the same fertilization capacity (e.g., motility and concentration) as younger males ( Watt et al 2021 ). In addition, it has also been shown that younger males produced more atypical spermatozoa than older males ( Watt et al 2021 ). Other complementary mechanisms could potentially involve size-specific macromolecular composition of spermatozoa affecting the duration of the first steps of fertilization (e.g., acrosome composition, chromatin unpacking) and/or the embryonic development ( Gusseck and Hedrick 1971 ; Lohka and Masui 1983 ; Carroll Jr et al 1991 ).…”
Section: Discussionmentioning
confidence: 99%